Predictive value of inflammatory and hematological data in diabetic and non-diabetic retinopathy - Atli, H.; Onalan, E.; Yakar, B.; Duzenci, D.; Donder, E. (Verduci Publisher, 2022)
OBJECTIVE: The current study aimed at investigating the predictive role of inflammatory, hematological and biochemical parameters in diabetic and non-diabetic retinopathy. MATERIALS AND METHODS: The cross-sectional study was conducted between June 2019 and September 2020. We included patients with diabetic retinopathy (proliferative DR=14, non-proliferative DR=16), patients with non-diabetic retinopathy (n=30), patients with Type 2 Diabetes Mellitus (T2DM) without retinopathy (n=30) and control group (n=30). Demographic, hematological, and biochemical parameters of the participants were examined. RESULTS: Participants' age and duration of diabetes mellitus were higher in proliferative and non-proliferative DR groups than patients with T2DM without retinopathy (p<0.001). There were significantly difference in terms of BMI (p<0.001), HbA1c (p<0.001), glucose (p<0.001), LDL (p<0.001), AST (p=0.001), hemoglobin (p<0.001), urea (p<0.001), creatinine (p<0.001), lymphocyte (p=0.001), and neutrophil (p=0.002) levels between groups. IL-6 levels were higher in proliferative DR, non-proliferative DR, and non-diabetic retinopathy groups than the control group. TNF-alpha levels were higher in proliferative DR and non-diabetic retinopathy groups than the control group. The NLR and PLR median values were significantly higher in the proliferative DR group than in other groups (p<0.001). CONCLUSIONS: The current study showed that IL-6 and TNF-alpha levels are elevated in diabetic and non-diabetic retinopathy. In addition, neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) median levels are higher in proliferative diabetic retinopathy than other groups. These findings support the inflammatory process may be accelerating the development of retinopathy.
Keywords: Diabetes mellitus; Retinopathy; Neutrophil/lymphocyte ratio; Platelet; lymphocyte ratio